The Effectiveness of Guided Reciprocal Peer Questioning (GRPQ) in Teaching Writing Viewed from Creativity - Furqon Edi Wibowo (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
The research method was experimental. The subject of the research is the second grade students of science 1 and the second grade students of science 2. Each of them consists of 30 students. The second grade students of science 2 are as experimental class who were taught using GRPQ technique and the second grade students of science 1 are as control class who were taught using Free Writing technique. The data were in the form of quantitative data and they were taken from a test. They are the scores of students’ writing test after having nine times treatment for each class. The researcher analyzed the data using ANOVA or analysis of variance and Tukey test. Based on the result of data analysis, the research findings are: (1) The GRPQ technique is more effective than Free Writing technique to teach writing for the second grade students of senior high school; (2) The writing skill achievement of the students having high creativity is better than that of those having low creativity; and (3) There is an interaction between teaching techniques and students’ creativity. Based on these research findings, it can be concluded that GRPQ technique is an effective technique to improve the writing skill of the second grade students of senior high school.